Global capitalism crisis fueling coups and instability in Africa - Alhinho, Júlia (Frontiers in Political Science, 2023)
In this paper, I try to show that the recent surge of coups in Africa, like past surges, rather than resulting from cultural factors, is closely linked with the cyclic crisis of capitalism to which Africa is especially vulnerable, compounded by inadequate decolonization and by structural adjustment programs imposed by the leaders of economic globalization. Looking into the instances of coups in the African continent over the past 50 years and the history of global capitalism, I try to show that there is a pattern of coups matching capitalism crisis. I will look into the example of Guinea-Bissau to show this linkage between crisis and coups and the incidental and adaptive role of the military and political elites in the context of economic globalization. Political instability and violent takeover of political authority in Africa and beyond- are, therefore, a symptom of what has gone wrong with neoliberal globalization. Like Rodrik, I conclude that this has placed humanity before the trilemma: economic globalization, democracy and national sovereignty cannot be achieved simultaneously. To overcome it, there is a need for unfettered public debate on what form of global governance we want.